Consensus on molecular imaging and theranostics in prostate cancer. Issue 12 (December 2018) - Fanti, Stefano; Minozzi, Silvia; Antoch, Gerald; Banks, Ian; Briganti, Alberto; Carrio, Ignasi; Chiti, Arturo; Clarke, Noel; Eiber, Matthias; De Bono, Johann; Fizazi, Karim; Gillessen, Silke; et al.
Summary: Rapid developments in imaging and treatment with radiopharmaceuticals targeting prostate cancer pose issues for the development of guidelines for their appropriate use. To tackle this problem, international experts representing medical oncologists, urologists, radiation oncologists, radiologists, and nuclear medicine specialists convened at the European Association of Nuclear Medicine Focus 1 meeting to deliver a balanced perspective on available data and clinical experience of imaging in prostate cancer, which had been supported by a systematic review of the literature and a modified Delphi process. Relevant conclusions included the following: diphosphonate bone scanning and contrast-enhanced CT are mentioned but rarely recommended for most patients in clinical guidelines; MRI (whole-body or multiparametric) and prostate cancer-targeted PET are frequently suggested, but the specific contexts in which these methods affect practice are not established; sodium fluoride-18 for PET-CT bone scanning is not widely advocated, whereas gallium-68 or fluorine-18 prostate-specific membrane antigen gain acceptance; and, palliative treatment with bone targeting radiopharmaceuticals (rhenium-186, samarium-153, or strontium-89) have largely been replaced by radium-223 on the basis of the survival benefit that was reported in prospective trials, and by other systemic therapies with proven survival benefits. Although the advances in MRI and PET-CT have improved the accuracy of imaging, the effects of these new methods on clinical outcomes remains to be established. Improved communication between imagers and clinicians and more multidisciplinary input in clinical trial design are essential to encourage imaging insights into clinical decision making.